Individual Differences in Revising (and Maintaining) Accurate and Inaccurate Beliefs About Childhood Vaccinations. Issue 5 (4th July 2019) - Kessler, Erica D.; Braasch, Jason L.G.; Kardash, Carolanne M.
ABSTRACT: This study examined relationships between several individual differences measures and belief revision after reading a text refuting common misconceptions about childhood vaccinations. Individual differences included preexisting accurate and inaccurate beliefs on the topic, prior knowledge about how vaccinations work, need for cognition, and flexible thinking. Dependent measures included an essay assessing vaccination support and a readministration of the preexisting topic beliefs inventory immediately after reading and after a 2-day delay. Multiple regression analyses demonstrated belief consistency effects in that preexisting accurate and inaccurate beliefs stably predict their postreading counterparts. Above and beyond these effects, readers higher in need for cognition were more likely to gain accurate beliefs about childhood vaccination at immediate and delayed time points. However, a backfire effect was also observed such that readers higher in flexible thinking were more likely to gain inaccurate beliefs, with concomitant lower values on accurate beliefs; this effect was present immediately and at a delay. The findings confirm that people can display a strong "myside bias" even when reading refutations, but that higher need for cognition affords opportunities for appropriate knowledge revision. At the same time, our findings suggest an alarming, potentially detrimental aspect of refutational texts: They may introduce opportunities for some learners to acquire novel misconceptions, especially if they are more flexible thinkers. Future directions of the current work are discussed.